2007
DOI: 10.1016/j.vetmic.2007.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Screening of pigs resistant to F4 enterotoxigenic Escherichia coli (ETEC) infection

Abstract: The present study analysed quantitatively the mucin 4 polymorphism for determing the F4ac/ab receptor status of a total of 63 pigs by comparing it with the in vitro villous adhesion assay. The probability of a susceptible genotype for the mucin 4 increases significantly with increasing F4ab or F4ac ETEC adhesion per 250 mm villi (P = 0.029 for F4ab, P = 0.030 for F4ac), with the odds ratio for each unit increase of F4ab or F4ac equal to, respectively, 1.036 (95% CI [1.004-1.069]) and 1.018 (95% CI [1.002-1.034… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…These piglets were from different sows and bound to have genetic variability, affecting the outcome of the experiment, of which the F4R status is particularly important. The mucin-4 gene polymorphism test increases the likelihood of identifying the F4R-positive piglets; however, the phenotypic expression of receptors largely varies, as it is believed to involve gene epistasis (22). Hence, the piglets were randomly assorted into four groups and the phenotypic expression of F4R was confirmed after euthanasia.…”
Section: Protective Effect Of Oral Feed-based Passive Immunization Inmentioning
confidence: 99%
“…These piglets were from different sows and bound to have genetic variability, affecting the outcome of the experiment, of which the F4R status is particularly important. The mucin-4 gene polymorphism test increases the likelihood of identifying the F4R-positive piglets; however, the phenotypic expression of receptors largely varies, as it is believed to involve gene epistasis (22). Hence, the piglets were randomly assorted into four groups and the phenotypic expression of F4R was confirmed after euthanasia.…”
Section: Protective Effect Of Oral Feed-based Passive Immunization Inmentioning
confidence: 99%
“…In practice, breeding programs with F4 receptor-negative pigs are feasible ways for controlling F4-expressing (F4 ϩ ) ETEC-related diarrhea, and a polymorphism in the mucin 4 gene (MUC4) has been developed to allow genotyping for determination of ETEC F4ab/ac receptor resistance or susceptibility. However, susceptibility toward ETEC F4ab/ac is not governed only by the MUC4 gene in pigs, since positive adhesion of F4ab/ac ETEC occurs in more than 30% of pigs of genotype MUC4 that are supposed to be ETEC F4ab/ac receptor negative (i.e., MUC4 resistant) and more receptors for F4 fimbriae have been discovered (8,9). We recently found that an F4 ϩ ETEC hybrid expressing virulence factors STb, LT, Stx2e, attaching and effacing intimin (eae), translocated intimin receptor (tir), escV, and E. coli-secreted protein A (espA) can also cause enteritis and/or fever in MUC4-resistant piglets (10).…”
mentioning
confidence: 99%
“…nterotoxigenic Escherichia coli (ETEC) strains are not only a common cause of postweaning diarrhea in piglets (1) but are also associated with children's and traveler's diarrhea (2,3). The most prevalent ETEC strains implicated in postweaning diarrhea express F4 (K88) ϩ fimbriae (4).…”
mentioning
confidence: 99%